The Attitude Virus: Curing Negativity at the Workplace - Shah, Rupa; Talati, Pinky (Prabandhan: Indian Journal of Management, 2013)
Negativity spreads like wildfire, and before anyone realizes what has happened, the entire workplace can be affected. This is not a physical illness, but it is the attitude that causes negativity in all it touches. It can affect the weak or powerful, the home or workplace, the worker or employer. Worst of all, if not discovered and eliminated quickly, the virus can spread to epidemic proportions, leading to loss of confidence, enthusiasm, creativity, productivity, and it is quite expensive for organizations too as it leads to absenteeism, increased turnover, decreased productivity, and lost revenues from customers taking their business elsewhere. This paper focuses on what is negativity, incivility, and finding preventive actions-"cures" for managing the negativity virus at organizations to remain competitive.